2022
DOI: 10.17309/tmfv.2022.2.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recreational Futsal on Body Composition in Passive Football Players

Abstract: The purpose of this study was to evaluate the impact of recreational futsal on passive middle-aged footballers in body composition.  Materials and methods. The research was conducted on a sample of 58 men aged from 30 to 40, average age 35.88 ± 2.39. The sample was divided into two groups. The first group included 29 passive football players (average age 35.58 ± 2.36) who were engaged in recreational futsal 2-3 times a week, and the second group included 29 passive football players (average age 36.17 ± 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…These results were reinforced by Bahari, Hanief, & Junaedi (2020) in their research that futsal extracurriculars were in the moderate category. Furthermore, research conducted on health students showed less (Maliqi et al, 2022), and also Physical Education students (Panchuk et al, 2022), as well as highland junior high school students (Firmansyah et al, 2021). Phys.…”
Section: Discussionmentioning
confidence: 99%
“…These results were reinforced by Bahari, Hanief, & Junaedi (2020) in their research that futsal extracurriculars were in the moderate category. Furthermore, research conducted on health students showed less (Maliqi et al, 2022), and also Physical Education students (Panchuk et al, 2022), as well as highland junior high school students (Firmansyah et al, 2021). Phys.…”
Section: Discussionmentioning
confidence: 99%